Management of the Game "Finger Painting" in Improving Fine Motor Skills In Early Childhood - Hefniy Hefniy; Chusnul Muali; Fatiatol Indanis; Nur Hidayati (Jurnal Obsesi : Jurnal Pendidikan Anak Usia Dini, 2022)
This study aimed to describe the management of finger painting games in improving fine motor skills in children with ingredients obtained and relatively inexpensive, namely dish soap concoction. The research method uses a qualitative approach to get an idea of the finger painting game (concoctions dishwashing soap) direct observations when doing finger painting at RA Maysitoh VI. Sources of information were obtained from interviews with school principals, teachers, parents, and students. The results showed; RA Maysitoh VI institution implements finger painting game management in stimulating students' motoric growth using, planning activities, implementing fun finger painting methods, and assessing children's development. The results obtained by playing finger painting (concoctions dishwashing soap) showed significant effects on children's motor skills as indicated by their interest in forming flowers, writing letters, and making patterns with their finger brushes. This finger painting activity indirectly trains the flexibility of the child's fingers in carrying out further fine motor activities such as writing, cutting, tearing, collage, and so on